2007
DOI: 10.3144/expresspolymlett.2007.8
|View full text |Cite
|
Sign up to set email alerts
|

Application of percolation model on the brittle to ductile transition for polystyrene and polyolefin elastomer blends

Abstract: Abstract. The percolation model was applied in the study of brittle to ductile transition (BDT) of polystyrene (PS) and polyolefin elastomer (POE) blends. Based on the interparticle distance and percolation model, stress volume (Vs) can be expressed by volume fraction (Vr) and ratio of the diameter of stress volume and the diameter of the domain (S/d). The percolation threshold (Vsc) varied from π/6 to 0.65. From the results of the Charpy impact strength of the blends, the percolation threshold for the brittle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
0
16
0
2
Order By: Relevance
“…The controllable properties based on the octene content, besides excellent processability of EOC, have widen its application areas. The results indicated that by applying the suitable compatibilization, EOC could desirably modify the toughness and the impact resistance of a wide range of thermoplastics such as PP, PET, polyamide 6, and PS . To the best of our knowledge, the role of nanoclay platelets as a compatibilizer for PS/EOC blend systems and how they affect the interfacial interactions between phases and their rheological and mechanical properties, besides their morphology, have not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…The controllable properties based on the octene content, besides excellent processability of EOC, have widen its application areas. The results indicated that by applying the suitable compatibilization, EOC could desirably modify the toughness and the impact resistance of a wide range of thermoplastics such as PP, PET, polyamide 6, and PS . To the best of our knowledge, the role of nanoclay platelets as a compatibilizer for PS/EOC blend systems and how they affect the interfacial interactions between phases and their rheological and mechanical properties, besides their morphology, have not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…The percolation model was used by Guo et al to investigate polystyrene=polyolefin elastomer blends. According to Guo, the percolation threshold of the POE content for BDT is 14 wt% in PS=POE blends [37] . In our investigation, the percolation threshold of the WF content for the brittle-ductile transition in the SBS-toughened WPCs is 15 wt%, which is close to the POE content in PS=POE blends.…”
Section: Results and Discussion Mechanical Propertiesmentioning
confidence: 99%
“…Percolation theories have been applied to describe the brittle-ductile transition of composites modified with elastomer [37][38][39][40][41][42] . The percolation model was used by Guo et al to investigate polystyrene=polyolefin elastomer blends.…”
Section: Results and Discussion Mechanical Propertiesmentioning
confidence: 99%
“…A Figura 7 apresenta a fotomicrografia do PS puro, no qual apresenta um aspecto liso e homogêneo, que está associado à natureza frágil deste polímero de baixa tenacidade. Além disso, observam-se estrias correspondentes as marcas e degraus deixados pela trinca responsável pela ruptura do corpo de prova e que foi nucleada a partir do entalhe [33]. Esta trinca que se propagou deixou marcas envolvendo pequenas cavidades (seta vermelha).…”
Section: Microscopia Eletrônica De Varreduraunclassified